A novel technique and detailed analysis of cars in Indian roads to adopt low ground clearance. Issue 10 (23rd August 2020) - Nagappan, M.; Vinoth Kanna, I.
ABSTRACT: As the front wheels of a car descend along the slope of a bump, the vehicle comes down due to inertia. This motion is dampened by the suspension system. The Indian cars with low ground clearance when moving over bumps tend to have their under chassis brushed by the road surface which is mostly harmless. But if the bumps are too steep, the under chassis takes a hit .The result is damage to the critical parts of the vehicle. So our idea is to develop a system that will detect the presence of elements (bumps, speed breakers, stones, etc., ) in the course of the vehicle that could possibly cause serious damage to the vehicle's under chassis and other critical parts. The system we propose aims to identify the presence of such unsafe obstacles. The system adopted for Indian cars will merely harden the suspension using MR damper to provide a small lift sufficient enough to the system. We aim to identify the presence of such unsafe obstacles. The system adopted for Indian cars will merely harden the suspension using MR damper to provide a small lift sufficient enough to get through the bumps.